Over-expression of Topoisomerase II Enhances Salt Stress Tolerance in Tobacco - John, Riffat; Ganeshan, Uma; Singh, Badri N.; Kaul, Tanushri; Reddy, Malireddy K.; Sopory, Sudhir K.; Rajam, Manchikatla V. (Frontiers in Plant Science, 2016)
Topoisomerases are unique enzymes having an ability to remove or add DNA supercoils and untangle the snarled DNA. They can cut, shuffle and religate DNA strands and remove the torsional stress during DNA replication, transcription or recombination events. In the present study, we over-expressed topoisomerase II (TopoII) in tobacco (Nicotiana tabaccum) and examined its role in growth and development as well as salt (NaCl) stress tolerance. Several putative transgenic plants were generated and the transgene integration and expression was conﬁrmed by PCR and Southern blot analyses, and RT-PCR analysis respectively. Percent seed germination, shoot growth and chlorophyll content revealed that transgenic lines over-expressing the NtTopoIIα-1 gene exhibited enhanced tolerance to salt (150 and 200 mM NaCl) stress. Moreover, over-expression of TopoII lead to the elevation in proline and glycine betaine levels in response to both concentrations of NaCl as compared to wild-type. In response to NaCl stress, TopoII over-expressing lines showed reduced lipid peroxidation derived malondialdehyde (MDA) generation. These results suggest that TopoII plays a pivotal role in salt stress tolerance in plants.